JUMLAH ATM DAN INDIKATOR EKONOMI: STUDI KASUS PADA OECD-16 - Sih Handika, Kharina Martha; Prestianawati, Silvi Asna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The OECD countries are countries that have rapid digital development, so this study aims to examine the influence of commercial bank branches, inflation, and broad money on the number of Automated Teller Machines (ATMs) in the OECD-16 countries during 2017-2020. This research uses a quantitative approach with panel data regression analysis method. The results of the study show that commercial bank branches has a positive and significant influence on the number of ATMs, while broad money has a negative and significant influence. Meanwhile, the inflation variable does not have a significant influence on the number of ATMs. This research is expected to provide a positive contribution to the banks in improving the quality of banking services that support the needs of customers by ensuring the level of security and comfort of customer transactions, as well as providing development of ATM features.